2016
DOI: 10.4103/0973-1075.191742
|View full text |Cite
|
Sign up to set email alerts
|

Cancer pain management in developing countries

Abstract: The World Health Organization estimated that more than 60% of the 14 million new cancer cases worldwide in 2012 were reported in the developing part of the world, including Asia, Africa, Central and South America. Cancer survival rate is poorer in developing countries due to diagnosis at late stage and limited access to timely treatment. Since the disease per se cannot be treated even with the best available treatment modalities, what remains important is symptom management and providing comfort care to these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…These findings are consistent with those of recent studies and systematic reviews [12,13,20,26,37,79,80,96]. Thus, it can be argued that due to these negative attitudes and lack of knowledge towards CPM, the management of cancer pain remains a major problem worldwide, especially in countries within Europe, Africa and Asia [13,26,52,75,76,81,92]. These could be due to lack of education and training about CPM among professionals and lack of general awareness and adequate level of knowledge about CPM among patients, caregivers and the public, as these were stated in all of the included studies.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consistent with those of recent studies and systematic reviews [12,13,20,26,37,79,80,96]. Thus, it can be argued that due to these negative attitudes and lack of knowledge towards CPM, the management of cancer pain remains a major problem worldwide, especially in countries within Europe, Africa and Asia [13,26,52,75,76,81,92]. These could be due to lack of education and training about CPM among professionals and lack of general awareness and adequate level of knowledge about CPM among patients, caregivers and the public, as these were stated in all of the included studies.…”
Section: Discussionsupporting
confidence: 88%
“…Certain factors such as psychosocial and socio-economical have been associated with cancer-related pain in low- and middle-income countries with inadequate assessment and management of cancer pain. 59 , 60 Limited studies so far have reported a clear understanding of psychosocial factors associated with cancer pain, especially in relation to aging with some studies reporting no relationship with age 61 63 and others reporting interference with age. For example, a study in 2012 demonstrated that advancing age results in an increased prevalence of cancer pain.…”
Section: Resultsmentioning
confidence: 99%
“…While the association of age-related psychosocial factors with pain is more or less prevalent in both developed and low-middle income countries, socio-economic factors such as fear and misconceptions regarding addiction to opioids for palliative care, lack of preventive strategies, poverty, illiteracy, and social stigma over the use of morphine are some of the additional factors associated with an increased prevalence of cancer-related pain in low- and middle-income countries. 59 For example, in India, despite WHO efforts on increasing awareness for analgesic use, little progress has been made in relieving pain in cancer patients (social stigma). 65 In another example in Nigeria, hospitals outside the commercial city of Lagos do not have morphine available and need additional expenses (travel costs) to make morphine accessible to smaller cities/areas; thus, lack of infrastructure and poverty attributes toward cancer-related pain since most of the small hospitals are unable to afford these additional expenses.…”
Section: Resultsmentioning
confidence: 99%
“…Although opioids are accepted as essential for cancer pain globally,[ 29 30 ] accessibility, and availability remains limited in India[ 2 31 32 ] as in various parts of the developing world. [ 33 34 ] In 2017, the NDPS Amendment of 2014 has not yet been incorporated in all Indian states even though the law simplified the needed laws for each state.…”
Section: Mplementation Of the A Mendedmentioning
confidence: 99%
“…[ 1 2 26 ] Education of the medical fraternity at every opportunity through workshops and online courses focusing on opioid availability, accessibility, and training for safe use should be widespread and ongoing. [ 1 26 31 37 ] We need to address the poor public awareness of palliative and end of life care,[ 38 ] so that they come to expect high quality of care.…”
Section: Mplementation Of the A Mendedmentioning
confidence: 99%